2021
DOI: 10.3390/pharmaceutics13111869
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Development of Oral Fast-Dissolving Films Loaded with Nanosuspension to Augment Paroxetine Bioavailability: In Vitro Characterization, Ex Vivo Permeation, and Pharmacokinetic Evaluation in Healthy Human Volunteers

Abstract: Paroxetine (PX) is the most potent serotonin reuptake inhibitor utilized in depression and anxiety treatment. It has drawbacks, such as having a very bitter taste, low water solubility, and undergoing extensive first pass metabolism, leading to poor oral bioavailability (<50%). This work aimed to develop and optimize palatable oral fast-dissolving films (OFDFs) loaded with a paroxetine nanosuspension. A PX nanosuspension was prepared to increase the PX solubility and permeability via the buccal mucosa. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…The film was dissolved in 5 mL of deionized water, and the pH was recorded with a digital pH meter (model: Vision Plus pH 6175, JENCO, San Diego, CA, USA) [ 27 ]. This study was repeated in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…The film was dissolved in 5 mL of deionized water, and the pH was recorded with a digital pH meter (model: Vision Plus pH 6175, JENCO, San Diego, CA, USA) [ 27 ]. This study was repeated in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that incorporating Tween 80 into the film can increase drug permeation. Since the surfactant created an elastic function that loosened or fluidized the mucosal membrane lipid bilayer and allowed the drug to incorporate into deeper layers of the biological membrane, leading to an increase in the drug permeability through the buccal mucosa [ 23 ]. No previous study used PEG-40H in oral film formulations, however, the recent study resulted that PEG-40H yielded a film effect that was similar to that of using P-80 as a surfactant.…”
Section: Resultsmentioning
confidence: 99%
“…It influences the film’s friability; however, both formulations (F-UBO and R) display good resistance. The moisture can be due to the solvent system used in the formulation or to the ingredients’ hygroscopic properties, especially the plasticizer ones [ 82 ]. PEG 400 presents high hygroscopicity due to its hydrophilic hydroxyl groups interacting with water [ 83 ], providing more sites for interactions and leading to moisture retention in the films.…”
Section: Discussionmentioning
confidence: 99%